Survival impact and safety comparison of pirfenidone and nintedanib for idiopathic pulmonary fibrosis: A meta-analysis - Arshad, Hafiz Muhammad Ehsan; Ali, Faaz; Babar, Anas; Raza, Muhammad Zain; Maqsood, Musab; Ameer, Akmal (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2025)
Background and aim: Idiopathic pulmonary fibrosis (IPF) is a severe restrictive lung disease affecting approximately 3 million people worldwide with two approved antifibrotics, nintedanib and pirfenidone, available for use. This review aims to compare their survival impact and safety profile. Methods: Two databases and two trial registers along with additional sources were searched for cohorts reporting IPF patients of any age or stage, receiving either pirfenidone or nintedanib. The Inverse-Variance and Mantel-Haenszel method along with either a fixed- or random-effects model was used for analysing survival and other dichotomous outcomes, respectively. Results: 23 cohorts were included. The pooled analysis showed that compared to pirfenidone, nintedanib group had similar survival (HR=1.12; 95%-CI:0.99-1.27; P=0.07), all-cause mortality (OR=1.11; 95%-CI:0.94-1.31; P=0.22), drug switches (OR=1.82; 95%-CI:0.69-4.78; P=0.22), and treatment discontinuations (OR=0.92; 95%-CI:0.60-1.41; P=0.70), higher odds of diarrhoea (OR=12.39; 95%-CI: 5.67-27.07; P<0.00001) and abnormal liver-function tests (OR=2.98; 95%-CI:1.92-4.61; P<0.00001), and lower odds of photosensitivity (OR=0.06; 95%-CI:0.01-0.25; P=0.0001), and skin-rash (OR=0.17; 95%-CI:0.08-0.34; P<0.00001). Conclusions: While both treatment groups had similar overall survival and all-cause mortality, the safety profiles of nintedanib and pirfenidone differed significantly, with nintedanib being associated with greater odds of liver toxicity and diarrhoea, and pirfenidone with photosensitivity and skin rash, suggesting they could be favoured in slightly distinct population groups. Further research is necessary to refine the current comprehension of these drugs and their optimal utilization in IPF treatment, particularly taking into account factors such as disease stage and sequential therapy